Economia solidária, plural e ética, na promoção do emprego, da cidadania e da coesão social - Maria da Conceição Pereira Ramos (Universidade do Porto, 2011)
We aim to characterise the social and solidarity economy, the tertiary sector and non-profit organisations, showing their importance within contemporary societies and how they are becoming increasingly visible in social sciences, through a multidisciplinary approach. In addition to presenting different theoretical conceptualisations and approaches to solidarity economics, we look at: the specific nature of the plural economy in local development and its potential for employment; its social and ethical responsibility in solidarity financing, in the promotion of citizenship and equity and in the construction of an alternative economic paradigm; the role of business citizenship in social inclusion and the development of initiatives that promote social entrepreneurship, microcredit and volunteer work. We conclude that it is important to consolidate an alternative economy not only economically, but also ethically and politically. The acute crisis in the job market, the vast inequalities and the risks of social exclusion mean that the various public and private actors in society need to find new ways to tackle social and community intervention. Solidarity economy has several benefits: it emphasises the promotion of employment, entrepreneurship and social and territorial development while strengthening social cohesion and citizenship and boosting the fight against unemployment and poverty. This type of economy poses both challenges and opportunities for innovation in its relations with the State and the civil society, as well as for reinventing the Welfare State itself.